ORGANIZATION OF THE EDUCATIONAL PROCESS ON THE BASIS OF MS TEAMS SERVICE AT THE PRE-UNIVERSITY STAGE OF LANGUAGE TRAINING FOR FOREIGNERS - Васецкая, Лариса; Черновол, Ольга (SWorldJournal, 2020)
The article examines the problem of introduction of modern interactive technologies in the educational process at the pre-university stage of language training of foreign citizens. The author’s experience of using Microsoft Office 365 cloud services in th